The Kindertransport contesting memory - Craig-Norton, Jennifer (Bloomington, Indiana : Indiana University Press, 2019)
"Jennifer Craig-Norton sets out to challenge celebratory narratives of the Kindertransport that have dominated popular memory as well as literature on the subject. According to these narratives, the Kindertransport was a straightforward act of rescue and salvation, with little room for dealing with deeper, more complex issues. Craig-Norton reveals that many children experienced difficulties with settlement, they were treated inconsistently by refugee agencies, their parents had various motives for giving them up, and their carers had complex reasons for taking them in. Against the grain of many other narratives, Craig-Norton emphasizes the use of archival sources, many of them newly discovered testimonial accounts and letters from Kinder to their families. This documentary evidence together with testimonial evidence allows Craig-Norton to offer compelling insights into the nature of interactions between children and their parents and caregivers. She shows readers a more nuanced and complete picture of the Kindertransport" --
A-17